Serum lipidome associates with neuroimaging features in patients with traumatic brain injury - Thomas, Ilias; Newcombe, Virginia F.J.; Dickens, Alex M.; Richter, Sophie; Posti, Jussi P.; Maas, Andrew I.R.; Tenovuo, Olli; Hyötyläinen, Tuulia; Büki, András; Menon, David K.; Orešič, Matej (Cell Press, 2025)
Summary
Acute traumatic brain injury (TBI) is associated with substantial abnormalities in lipid biology, including changes in the structural lipids that are present in the myelin in the brain. We investigated the relationship between traumatic microstructural changes in white matter from magnetic resonance imaging (MRI) and quantitative lipidomic changes from blood serum. The study cohort included 103 patients from the CENTER-TBI study. Diffusion tensor fitting generated fractional anisotropy (FA) and mean diffusivity (MD) maps for the MRI scans while ultra-high-performance liquid chromatography quadrupole time-of-flight mass spectrometry was applied to analyze the lipidome. Increasing severity of TBI was associated with higher MD and lower FA values, which scaled with different lipidomic signatures. There appears to be consistent patterns of lipid changes associating with the specific microstructure changes in the CNS white matter, but also regional specificity, suggesting that blood-based lipidomics may provide an insight into the underlying pathophysiology of TBI.